EFFECTIVENESS OF VARIOUS CONCENTRATIONS OF LEMONGRASS LEAF EXTRACT LOTION (Cymbopogon nardus) AS REPELLENT OF AEDES AEGYPTI MOSQUITOES - Firda Ro'in; Agus Subagiyo; Arif Widyanto; Nur 'Aini (Buletin Keslingmas, 2020)
Effectiveness Of Various Concentrations Of Lemongrass Leaf Extract Lotion (Cymbopogon nardus) As Repellent Of Aedes aegypti Mosquitoes. Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue virus which is transmitted through the bite of the Aedes aegypti mosquito. Vector control efforts that are popular in the community are using chemical insecticides. The use of insecticides can cause mosquito resistance and cause poisoning in humans. Then effective controls need to be developed to avoid these impacts. Safe control of health and environmentally friendly is to use natural repellent derived from plants, one of which is lemongrass leaf (Cymbopogon nardus). The purpose of this study is to know the effectiveness of various concentrations of lemongrass leaf extract lotion (Cymbopogon nardus) as repellent of Aedes aegypti mosquitoes. This type of research is an experimental laboratory with the research design of The Posttest - Only Controlled Group Design. The research method by hand control and treatment is presented in a cage containing 25 Aedes aegypti mosquitoes for 6 hours with repetition 10 times each hour. The results showed that a concentration of 20% had an average protective capacity of 82.8%, a concentration of 40% had an average protective capacity of 95.0%, an concentration of 80% had an average protective capacity of 98.1% and lotion repellent from chemicals with the brand "X" has an average protection capacity of 88.6%. The results of the Kruskal Wallis analysis proved significant with p = 0.003 α (0.05), so there were significant differences in the protective power. The conclusion of the study was that the lemongrass leaf extract lotion was effectively used as a repellent of Aedes aegypti mosquitoes at a concentration of 40% and 80% because the protective power value 90% even though it had been used for 6 hours.